Fungsi Humas dalam Pengelolaan Lembaga Pendidikan - Tambunan, Rini Kurnia; Amel, Neng Liya Raisya; Hikmah, Siti Nurul; Aliyah, Rusi Rusmiati (Indo-MathEdu Intellectuals Journal, 2026)
Public Relations (PR) is a strategic element in the management of educational institutions because it plays a role in building the image of the institution, managing public communication, and strengthening public trust and participation. However, in the digital age and the 4.0 industrial revolution, the implementation of PR functions in educational institutions faces various challenges, especially related to the use of digital media and human resource competencies. This study aims to analyse the role, functions, and challenges of public relations in educational institutions in the digital era. The method used is a literature review by examining various scientific sources, in the form of journal articles and books relevant to educational public relations management. The results of the study show that professional public relations management, supported by human resource competencies, strategic use of social media, continuous performance evaluation, and the application of good ethics and crisis management, contribute positively to improving the quality and reputation of educational institutions. The conclusion of this study emphasises that public relations has a strategic position in supporting the sustainability, competitiveness, and public trust in educational institutions amid ongoing social and technological changes.